PERAN SEKTOR KEUANGAN DALAM PENGENTASAN KEMISKINAN DI INDONESIA - Sovia Dewi, Aliasuddin, M. Shabri Abdul Majid. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract: This study aims at analyzing the role of financial development on poverty alleviation in Indonesia using annual data for the period of 1980-2014. The ARDL approach to cointegration is used to empirically examine the existence of long run equilibrium between financial development and poverty reduction. Additionally the VECM Granger Causality approach is used to detect the direction of the causal relationship between financial development and poverty reduction. Meanwhile, to measure the duration and magnitude of poverty in response to the relative strength of the financial development shocks the impulse response Functions (IRFs) and Variance decompositions (VDCs) were used. Money supply and domestic credit to the private sector ratio were used as the indicators for financial development while poverty measured by household consumption expenditure per capita, and economic growth measured by Gross Domestic Product (GDP) per capita. Our findings showed that there was a long run relationship between financial development, economic growth and poverty reduction in Indonesia. Furthermore, our result showed that there was a bidirectional between financial development and poverty reduction. Money supply and the ratio of private credit in poverty reduction were positively contributed by the innovative shocks stemming in poverty reduction. Therefore, to accelerate poverty reduction, the goverment may adopt a policy requiring all commercial banks to provide a certain percentage of loans to the SMEs (Small and Medium sized Enterprises) that will be helpfull for reducing poverty throug creating employment opportunities to growth. Keywords : Financial Development, Poverty, Growth, ARDL, VECM, Abstrak: Penelitian ini bertujuan untuk menganalisis peran sektor keuangan terhadap pengentasan kemiskinan di Indonesia dengan menggunakan data tahunan untuk periode 1980-2014. Pendekatan ARDL untuk kointegrasi digunakan untuk membuktikan adanya keseimbangan jangka panjang antara sektor keuangan dengan pengentasan kemiskinan. Selain itu pendekatan VECM Kausalitas Granger digunakan untuk mendeteksi arah hubungan kausal antara sektor keuangan dan kemiskinan. Sementara itu, untuk mengukur jangka waktu dan besarnya kekuatan relatif kemiskinan dalam menanggapi guncangan yang dialami sektor keuangan digunakan Impulse Response Functions (IRFs) dan Variance Decompositions (VDCs). Jumlah uang beredar dan rasio kredit domestik untuk sektor swasta digunakan sebagai indikator pengembangan sektor keuangan, sementara itu kemiskinan diukur dengan pengeluaran konsumsi rumah tangga per kapita dan pertumbuhan ekonomi diukur dengan Produk Domestik Bruto (PDB) per kapita. Hasil penelitian menunjukkan bahwa ada hubungan jangka panjang antara sektor keuangan, pertumbuhan ekonomi dan pengentasan kemiskinan di Indonesia. Selanjutnya, hasil menunjukkan adanya hubungan kausalitas dua arah antara sektor keuangan dengan kemiskinan. Kontribusi jumlah uang beredar dan rasio kredit swasta adalah positif dalam merespon guncangan yang berasal dari kemiskinan. Oleh karena itu, untuk mempercepat pengentasan kemiskinan, pemerintah dapat mengambil kebijakan untuk menuntut semua bank-bank komersial menyediakan fasilitas kemudahan akses pinjaman bagi kelompok miskin dan Usaha Mikro, Kecil dan Menengah (UKM). Melalui kebijakan tersebut akan membantu untuk mengurangi kemiskinan melalui penciptaan kesempatan kerja dan pada akhirnya akan mengarah kepada peningkatan pertumbuhan ekonomi. Kata kunci : Sektor Keuangan, Kemiskinan, Pertumbuhan Ekonomi, ARDL, VECM.